2012
DOI: 10.4081/gh.2012.108
|View full text |Cite
|
Sign up to set email alerts
|

Modelling spatial concordance between Rocky Mountain spotted fever disease incidence and habitat probability of its vector Dermacentor variabilis (American dog tick)

Abstract: Abstract. The spatial distribution of Dermacentor variabilis, the most commonly identified vector of the bacterium Rickettsia rickettsii which causes Rocky Mountain spotted fever (RMSF) in humans, and the spatial distribution of RMSF, have not been previously studied in the south central United States of America, particularly in Texas. From an epidemiological perspective, one would tend to hypothesise that there would be a high degree of spatial concordance between the habitat suitability for the tick and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…distribution are poorly understood, as is their range of host species [44, 81]. Yet, it has previously been found that spotted fever incidence in humans, caused by R. ricketsii , is highest in suboptimal tick habitats [82]. This is in line with our findings and suggests that Rickettsia spp.…”
Section: Discussionsupporting
confidence: 90%
“…distribution are poorly understood, as is their range of host species [44, 81]. Yet, it has previously been found that spotted fever incidence in humans, caused by R. ricketsii , is highest in suboptimal tick habitats [82]. This is in line with our findings and suggests that Rickettsia spp.…”
Section: Discussionsupporting
confidence: 90%
“…Geographically weighted regression (GWR) can be used for these two considerations and can often produce improved models that enable better spatial inference and prediction. Recent studies have applied GWR modeling to drug-resistant tuberculosis versus risk factors (Liu et al, 2011); environmental factors versus typhoid fever (Dewan et al, 2013); local climate and population distribution versus hand, foot, and mouth disease (Hu et al, 2012); and environmental factors and tick-borne disease (Atkinson et al, 2012; Atkinson et al, 2014; Wimberly, Baer & Yabsley, 2008; Wimberly et al, 2008), all showing that predictor variables varied spatially across large geographic regions, implying that the results for such studies may be improved using GWR.…”
Section: Introductionmentioning
confidence: 99%
“…Manuscript to be reviewed tuberculosis versus risk factors (Liu et al 2011); environmental factors versus typhoid fever (Dewan et al 2013); local climate and population distribution versus hand, foot, and mouth disease (Hu et al 2012); and environmental factors and tick-borne disease (Atkinson et al 2012;Atkinson et al 2014;Wimberly et al 2008a;Wimberly et al 2008b), all showing that predictor variables varied spatially across large geographic regions, implying that the results for such studies may be improved using GWR.…”
Section: Introductionmentioning
confidence: 99%